Implementation Of Protection Of Traditional Cultural Expression In West Lampung Regency - Erlina B (IHSA Institute, 2022)
The West Lampung Regency Government has cultural potential in which it contains Traditional Cultural Expressions (hereinafter referred to as EBT) in various types and cultural values ??and local wisdom are maintained in each particular indigenous group. Such as traditional dances, traditional ceremonies, and traditions that grow in the people of West Lampung. The position of the state as the copyright holder of NRE is contained in the provisions of Article 38 paragraph 1 of Law Number 28 of 2014 concerning Copyright. The state is obliged to take inventory, maintain, and maintain NRE as mandated by Article 38 paragraph (2) of the Copyright Law. The problem in this study is, how is the state's control over traditional cultural expressions in Indonesia and how is the implementation of the protection of traditional cultural expressions in West Lampung Regency in particular. This research is an empirical juridical research. From the results of the study found the fact that state control has been carried out through an inventory carried out by the Ministry of Law and Human Rights in collaboration with the Ministry of Education and Culture, but there are still many local governments that have not protected knowledge and traditional cultural expressions to the fullest where there are no legal, institutional and cultural arrangements. legal culture that supports the protection of traditional cultural expressions, including West Lampung Regency whose implementation of the protection of traditional cultural expressions has not been optimal.